Perceived parenting style and self-perception in children with attention deficit/hyperactivity disorder - Maria Fernanda Molina (Universidad de San Buenaventura, 2015)
Background: there is a growing interest in the study of the self-perceptions of children with Attention Deficit/Hyperactivity Disorder (ADHD) and the bias in their self-concept. Goal: to explore how ADHD children’s perception of parenting style predicts their self-perception and the bias in self-concept. Method: Participants: children between 7 and 13 years old diagnosed with ADHD, children assisting to psychotherapy without an ADHD diagnose, and children not assisting to psychotherapy. It also participated one of their parents. Data analysis: It was used simple logistic regressions. Groups were studied separately. Results: maternal pathological control was the main predictor of ADHD children’s positive self-perceptions and bias. In the comparison groups it predicts negative self-perceptions. Results are discussed in the light of self-protection hypothesis.